Estimasi Nilai Evapotranspirasi Potensial dalam Rangka Optimalisasi Pemanfaatan Irigasi Permukaan di Kabupaten Wajo - Samsuar Samsuar; Husnul Mubarak; Nunik Lestari (Jurnal Agritechno, 2022)
Indonesian government is trying to increase the production of agricultural commodities in order to support the food self-sufficiency program. To support this program, the availability of irrigation facilities is important in supporting the productivity of agricultural field. Climate change and changes in agricultural systems have an impact on changes in the need of irrigation water in crop cultivation. The decreasing availability of water for agriculture encourages us to be able to use water more efficiently, especially for irrigation water. The purpose of this research is to predict the ETp value as a basis for determining plant water requirements, to determine the most suitable ETp model, to validate the prediction results of ETp values ​​using direct measurements in the field, and to obtain information related to climate factors that have the most influence on the ETp rate. The measurement of the ETp value is based on the use of Merra-2 global climate data and climate data from field measurements. ETp models used are Blaney-Criddle, Hargraves, Remanenko, Penman and Penman-Monteith. Research results showed that the ETp rate in Wajo District tended to increase during the July-October period indicating an increase in water demand in crop cultivation. The most influential climate parameter in determining the Penman Monteith ETp rate is solar radiation. The results of the ETp analysis using global data show that the Penman model is the closest model to the Penman Monteith ETp model from field measurements.